Long-lasting TMS motor threshold elevation in mild traumatic brain injury - Tallus, J.; Lioumis, P.; Hämäläinen, H.; Kähkönen, S.; Tenovuo, O. (Acta neurologica Scandinavica, 2012)
Tallus J, Lioumis P, Hämäläinen H, Kähkönen S, Tenovuo O. Long‐lasting TMS motor threshold elevation in mild traumatic brain injury.  Acta Neurol Scand: 2012: 126: 178–182.  © 2011 John Wiley & Sons A/S. Objectives –  Mild traumatic brain injury (mTBI) is very common, and part of the patients experience persistent symptoms. These may be caused by diffuse neuronal damage and could therefore affect cortical excitability. The motor threshold (MT), measured by transcranial magnetic stimulation (TMS), is a measure of cortical excitability and cortico‐spinal tract integrity. Materials and methods –  We used navigated TMS (nTMS) and electromyography to determine subjects’ left hemisphere MTs. Nineteen subjects with mTBI (11 with persistent symptoms and eight fully recovered) and nine healthy controls were tested. The injuries had occurred on average 5 years earlier. All participants had normal brain MRIs, that is, no signs of injury. None used centrally acting medication. Results –  The mean MT in controls was 43.0% (SD 2.5) of maximum stimulator output. The mTBI subjects mean MT was 53.4% (SD 9.7), being higher than the controls’ threshold. Subjective recovery did not correlate with MT. Conclusions –  The results show chronic MT elevation in a sample of subjects with symptomatic or recovered mTBI. This suggests that mTBI may be compensated, although not fully recovered, years after the injury. While the cause for MT elevation cannot be concluded from these preliminary observations, possible explanations include decreased cortical excitability and impaired subcortical conduction.